Hubungan Jenis Kelahiran Dengan Kejadian Asfiksia Bayi Baru Lahir Pada Ibu Bersalin Dengan Ketuban Pecah Dini di Rsud dr. R Soeprapto Cepu - Heriyanti Widya Widyaningsih (Jurnal Keperawatan Muhammadiyah, 2023)
Asphyxia of newborns can be caused by four factors, namely maternal factors, placental factors, fetal factors and delivery factors. The number of asphyxia cases of newborns with pregnancy complications in 2021 is 30 cases and in 2022 there are 39 cases. The number of cases of deliveries with Premature Ruptured Membranes (KPD) at Dr R Soeprapto Cepu General Hospital for the period (January – November 2022) was 311 with 87.3% being delivered by action (SC) and the remaining 12.7% being vaginal deliveries. This type of research is analytic observational. The design uses a cross sectional design. The research sample consisted of 360 people, which is 100% of the total population of mothers with KPD at Dr.R Soeprapto Cepu General Hospital, January 1 - December 31, 2022. The research instrument used a data collection format using a checklist. Data analysis using univariate using percentages and bivariate with chi square. The proportion of newborns with moderate asphyxia was mostly experienced by mothers giving birth to KPD with the type of action delivery, namely as many as 92 people (40.9%). The proportion of babies born with severe asphyxia was mostly experienced by mothers giving birth to KPD with the type of action delivery, namely as many as 82 people (36.4%). It can be concluded that there is a significant relationship between the type of delivery and the incidence of neonatal asphyxia in patients with premature rupture of membranes at dr. R Soeprapto Cepu (p = 0.000 <0.05).